2022
DOI: 10.1128/spectrum.01714-22
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Mycobacterium abscessus Isolates Recovered from German Cystic Fibrosis Patients

Abstract: Mycobacterium abscessus is a major respiratory pathogen in cystic fibrosis (CF) patients. Recently it has been shown that dominant global clonal complexes (DCCs) have spread worldwide among CF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Some of these cases have appeared as outbreaks, sometimes related to contaminated environmental sources [ 95 , 96 , 97 , 98 ]. The introduction of molecular epidemiology tools has been of great importance for the characterization of these outbreaks because the phenotypic characteristics of this mycobacterium are so common that strain differentiation must be carried out by molecular analysis [ 11 , 97 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these cases have appeared as outbreaks, sometimes related to contaminated environmental sources [ 95 , 96 , 97 , 98 ]. The introduction of molecular epidemiology tools has been of great importance for the characterization of these outbreaks because the phenotypic characteristics of this mycobacterium are so common that strain differentiation must be carried out by molecular analysis [ 11 , 97 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of WGS has markedly advanced our comprehension of NTM antibiotic resistance, thus improving treatment strategies. In a significant validation of WGS's precision, Wetzstein et al (166) demonstrated complete concordance between WGS forecasting of M. abscessus resistance to macrolides and aminoglycosides and results from both GenoType NTM-DR kits and phenotypic DST. Lipworth et al (167) leveraged sequencing data from M. abscessus to identify novel mutations in the erm gene and rrs gene linked to macrolide resistance, mutations not covered by traditional genotyping, raising the possibility of false-negative outcomes.…”
Section: Exploring Molecular Diagnostics For Ntm Infections: Beyond P...mentioning
confidence: 99%
“…43 Some studies have demonstrated clonally related strains in patients attending the same clinic 38,39,[44][45][46] and others have not. [47][48][49] DCC strains are not restricted to pwCF and have been frequently identified in patients with other respiratory diseases. 43,50 A national UK healthcare utilization database assessed potential contact between patients.…”
Section: Acquisition and Transmissionmentioning
confidence: 99%